2013
DOI: 10.1021/ef400460d
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Decoupling Methodology for Development of Skeletal Oxidation Mechanisms for Heavy n-Alkanes from n-Octane to n-Hexadecane

Abstract: A series of skeletal mechanisms was developed based on a decoupling methodology to describe the oxidation of n-alkanes from n-octane to n-hexadecane. In the decoupling methodology, a fuel oxidation mechanism is divided into two parts: one is an extremely simplified model for species with a carbon atom number larger than two to simulate the ignition characteristics of n-alkane; the other is a detailed mechanism for H2/CO/C1 to predict the concentrations of small molecules, laminar flame speed, and extinction st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…The decoupling methodology has shown good performance in developing skeletal mechanisms for n-alkanes [22,25] and iso-alkanes [26]. Because of the different molecular structure between alkanes and methyl esters, necessary modifications were conducted for the construction of mechanisms for MD and MD5D by introducing a skeletal sub-mechanism containing the ester group in this study.…”
Section: Skeletal Oxidation Mechanism For Biodiesel Surrogatementioning
confidence: 99%
“…The decoupling methodology has shown good performance in developing skeletal mechanisms for n-alkanes [22,25] and iso-alkanes [26]. Because of the different molecular structure between alkanes and methyl esters, necessary modifications were conducted for the construction of mechanisms for MD and MD5D by introducing a skeletal sub-mechanism containing the ester group in this study.…”
Section: Skeletal Oxidation Mechanism For Biodiesel Surrogatementioning
confidence: 99%
“…Till now, other experimental ignition delay data for n-undecane in air are not available. The comparisons of current results with simulations based on LLNL 15 mechanism, mechanism of Mzé-Ahmed et al 17 , mechanism of Chang et al 18 and JetSurF2.0 mechanism 19 are shown in Fig.4 for high temperature condition and in Fig.3 mainly for low temperature condition. As shown in Fig.4(a) and (b), predictions of the JetSurF2.0 mechanism, the LLNL mechanism, and the mechanism of Mzé-Ahmed et al are in closer accord with current experimental data, and in Fig.4(c), the computed ignition delay times from the LLNL mechanism are in good agreement with measured data.…”
Section: Comparison With Mechanism Predictionsmentioning
confidence: 84%
“…Mzé-Ahmed et al 17 have studied the oxidation kinetic model of n-undecane and n-dodecane in a Jet-Stirred Reactor. Chang et al 18 have also developed skeletal oxidation mechanisms for heavy n-alkanes from n-octane to nhexadecane. These mechanisms can be applied to high and low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced C 2 -C 3 mechanism serves as the transition between the skeletal large-molecule mechanism and the detailed H 2 /CO/C 1 mechanism. With the decoupling methodology, a series of skeletal mechanisms for normal and branched alkanes have been constructed (Liu et al, 2012;Chang et al, 2013b). By comparing with experimental data, it is found that the mechanisms can satisfactorily reproduce the auto-ignition and oxidation behaviors from low to high temperatures in various reactors and practical engines.…”
Section: Decoupling Methodologymentioning
confidence: 99%